PENGARUH KOMPENSASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada PT. West Globalindo District Jawa Tengah) - Herdi Praptono, 06.05.51.0094 (Students Journal of Economic and Management, 2014)
This study aimed to examine the effect of compensation, motivation and discipline to the performance of employees of PT. West Globalindo District Central Java.The population in this study were all employees of PT. WEST GLOBALINDO District Central Java , amounting to 135 people. Saturated sample is census, where all members of the population sampled. So in this case, samapel taken in this study amounted to 135 people. Data analysis techniques are used to solve problems in this research is the use of regression analysis.The results showed that there is a positive and significant effect of the variable compensation (X1) on employee performance variable (Y). There is a positive and significant influence of motivational variables (X2) on employee performance variable (Y . There is a positive and significant effect of the variable labor discipline ( X3) on employee performance variable (Y). Keywords : Compensation, Motivation, Work Discipline, Employee Performance